A Study On Customer-Supplier Relationship (Trust, Communication And Commitment) For Manufacturing Firms In Penang From The Perspective Of Supply Chain Management Measures - THOO, MIN HAI (2004)
Supply Chain Management (SCM) performance and customer-supplier relationships have been seen as two separate subjects. While relationship factors have been proven to be important to improve the business process, interlink between relationships and SCM performance has not been focused extensively.